Propagation of three native Brazilian Piper species by cuttings and indole butyric acid - Ferriani, Aurea Portes; Deschamps, Cícero; Amaral, Wanderlei Do; Silva Neto, Carlos de Melo E. (Universidad Pedagógica y Tecnológica de Colombia, 2019)
1 recurso en línea (páginas 491-499)